Numerical Solution of Calculus of Variations by using the Second Chebyshev Wavelets - Suha Najeeb Shihab; Asmaa Abdalelah Abdalrehman (Engineering and Technology Journal, 2012)
In this paper the second Chebyshev wavelets expansions with the operational matrix is applied for solving calculus of variational problems , with the aid of spectral method to reduce the variational problems in to a solution set of algebraic equations . Finally, numerical examples are present to show the validity and efficiency of the technique